Hosts, guests and politics: Coastal Resorts Morphological Change - Andriotis, Konstantinos (My University, 2006)
Resort morphology goes through a predictable sequence of stages: from pre-tourism low through high-density development to an urbanized state. Three elements are considered essential in such coastal resorts change: hosts, guests, and politics. Using historical data from the mass-developed Greek island of Crete, ten principal characteristics are identified as determinants of the morphological change of coastal resorts. A temporal model of unplanned change is also proposed. Although the study was constrained by limited data availability, the proposed model is deemed able to represent the morphological change of Cretan mass-developed coastal resorts.
Keywords: Hosts; Guests; Politics; Morphology; Urbanization; Coast